Daughter of lies eaudiobook - Davidson, Kenley (Andari Chronicles, 2020)
A romantic fantasy inspired by Snow White . . . Brenna Seagrave doesn't want to be a countess. She prefers her life of danger and disguise as a spy for the kingdom of Andar, but the Andari court isn't quite ready for a countess who engages in espionage. Feeling trapped, Brenna accepts an invitation to a mysterious estate, where she hopes to connect with the mother she's never had a chance to know. But nothing is quite as Brenna expects. Her mother is obsessively critical, the neighbor is a ridiculous flirt and the handsome butler is undoubtedly up to something. Also, someone seems to be plotting her demise. Brenna can't go home until she finds out who wants to kill her, but her only allies are a bumbling nobleman and an old acquaintance who isn't exactly a team player. In this game of secrets and lies, no one is who they pretend to be—not even Brenna—but they must still work together to uncover the truth. If they fail, it's only a matter of time before Brenna's past catches up with her, and either she or someone she loves ends up dead.